Performance Comparison of Software Reliability Estimation Algorithms - Yano, Hiromu; Dohi, Tadashi; Okamura, Hiroyuki (Computer, 2024)
Specific optimization algorithms have been developed for the purpose of automated software reliability assessment tools. In this article, we propose the Monte Carlo expectation-maximization algorithm as another optimization algorithm, and carry out the performance comparison of the software reliability estimation algorithms through comprehensive numerical experiments.